CO2NTROL: a new technology for monitoring stored grains - Bartosik, Ricardo Enrique; De La Torre, Diego (Estación Experimental Agropecuaria Balcarce, INTA, 2025)
The National Institute of Agricultural Technology (INTA) along with the company “Ingenieria Electrónica Argentina” (IEA) from the city of Rosario (Arg.) have developed a new technology for monitoring grains stored in bins and flat storage units (warehouse). The goal of measuring CO is to identify this biological 2 activity at its early stages, before it leads to a decline in grain quality